2019
DOI: 10.5267/j.msl.2019.5.030
|View full text |Cite
|
Sign up to set email alerts
|

Predicting customers' online word of mouth intention: The theory of planned behavior applied to understand youth Saudi social media behaviors

Abstract: Word of mouth (WOM) is the oldest, yet still a very common form of marketing. Over the years, it has undergone under significant transformation as a result of the changing business strategies and rapid improvement in technology. Today, WOM has gained traction as a very effective and economic form of advertisement. With the increase in the use of internet technology and use of social media for marketing, online word of mouth (OWoM) is significantly changing the sphere. Today, many marketers prefer to use OWoM t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…After tracing the importance of content marketing, we do not find any research in the health sector of Saudi Arabia addressing multi-dimensional relationships among content marketing and clients' engagement, trust and loyalty. Although, some studies have investigated the issues regarding usage of social media, word of mouth and Corporate Social Responsibility (CSR) in the sectors other than health sector (Ajina et al, 2019;Ajina, 2019a;Ajina, 2019b). But the Saudi health sector literature is still silent towards the very important multi-dimensional relationships amongst content marketing and clients' engagement, loyalty and trust.…”
Section: Introductionmentioning
confidence: 99%
“…After tracing the importance of content marketing, we do not find any research in the health sector of Saudi Arabia addressing multi-dimensional relationships among content marketing and clients' engagement, trust and loyalty. Although, some studies have investigated the issues regarding usage of social media, word of mouth and Corporate Social Responsibility (CSR) in the sectors other than health sector (Ajina et al, 2019;Ajina, 2019a;Ajina, 2019b). But the Saudi health sector literature is still silent towards the very important multi-dimensional relationships amongst content marketing and clients' engagement, loyalty and trust.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the audience can generally identify well with influencers (Schouten et al, 2020), which may serve as a confirmation of their credibility as sources when it comes to the subjects in which they are considered experts. Other researchers also included source credibility within the scope of subjective norms (see Aditami, 2016;Ajina, 2019). However, gaming influencers can, theoretically, do more than that.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been limited research employing the TPB to assess individuals' WOM intention toward organizations. Although some researchers found attitudes toward WOM, subjective norm, and PBC were positively associated with WOM intention (Fu et al, 2015), other researchers found no significant relationship between intention and subjective norms (Ajina, 2019) or PBC (Overton et al, 2020). The inconsistent findings may result from the context between previous studies.…”
Section: The Determinants Of Csa Supportmentioning
confidence: 92%
“…Pan and Truong (2018) also found that self-efficacy but not perceived controllability positively predict individuals' intention to use low-cost airlines. When it comes to WOM intention, some researchers reported positive relationships between the self-efficacy and WOM intention (Cheung and Lee, 2012) whereas others found negative relationships between perceived controllability and WOM intention (Ajina, 2019) as well as no significant relationship between perceived controllability and WOM intention (De Canni ere et al, 2009). Given the different roles in determining WOM intention between self-efficacy and perceived controllability, we pose the following.…”
Section: Self-efficacy and Perceived Controllability As Perceived Beh...mentioning
confidence: 97%